The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1055/s-0033-1364169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Level of Dysphagia, Anxiety, and Nutritional Status Before and After Speech Therapy in Patients with Stroke

Abstract: Introduction: The rehabilitation in oropharyngeal dysphagia evidence-based implies the relationship between the interventions and their results. Objective: Analyze level of dysphagia, oral ingestion, anxiety levels and nutritional status of patients with stroke diagnosis, before and after speech therapy. Method: Clinical assessment of dysphagia partially using the Protocol of Risk Assessment for Dysphagia (PARD), applying the scale Functional Oral Intake Scale for Dysphagia in Stroke Patients (FOIS), Beck Anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The professional groups carrying out the screenings were reported in only 6 studies (Nursing staff/study nurse: Cabre et al 2010; Carrión et al 2015; Mateos-Nozal et al 2017; Shimazu et al 2020; SLT: Crary et al 2006; Moncayo-Hernandéz et al 2023) [ 10 , 43 46 , 49 ]; 7 studies used exclusively self-reported tools (Manas-Martinez et al 2018; Matsuo et al 2017; Popman et al 2016; Tran et al 2021; Vidal Casariego et al 2020; Wakabayashi & Matsuhima 2016; Wham et al 2017) [ 41 , 47 , 50 , 57 , 58 , 60 , 67 ] and the remaining 14 did not specify the profession [ 13 , 42 , 48 , 51 56 , 59 , 61 , 68 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The professional groups carrying out the screenings were reported in only 6 studies (Nursing staff/study nurse: Cabre et al 2010; Carrión et al 2015; Mateos-Nozal et al 2017; Shimazu et al 2020; SLT: Crary et al 2006; Moncayo-Hernandéz et al 2023) [ 10 , 43 46 , 49 ]; 7 studies used exclusively self-reported tools (Manas-Martinez et al 2018; Matsuo et al 2017; Popman et al 2016; Tran et al 2021; Vidal Casariego et al 2020; Wakabayashi & Matsuhima 2016; Wham et al 2017) [ 41 , 47 , 50 , 57 , 58 , 60 , 67 ] and the remaining 14 did not specify the profession [ 13 , 42 , 48 , 51 56 , 59 , 61 , 68 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both describe the screening process as part of routine patient care and report on specific measures derived from the screening results, such as a referral to swallowing of nutritional specialists or a recommendation on texture for oral nutrition. Five studies reported that screening was systematically repeated, either after an intervention, after a certain amount of time or right before discharge [ 51 , 55 , 56 , 68 , 69 ]. Table 5 provides an overview of the subsequent intervention following positive screening results.…”
Section: Resultsmentioning
confidence: 99%
“…OD is identified as a major contributor to malnutrition according to a resolution of the Council of Europe ( 19 ) and some other investigators ( 20 22 ). Therefore, it is impertinent to identify patients who are at risk of malnutrition and to initiate appropriate nutritional treatment.…”
Section: Discussionmentioning
confidence: 99%